Aplicación de una auditoría tributaría a la cooperativa de ahorro y crédito “Sumak Kawsay”, ubicada en el cantón Latacunga, provincia de Cotopaxi, en el período enero – diciembre 2011 - Troya Tasigchana, Fausto Rolando (2015)
This research was conducted based on a conceptual analysis of the procedures and criteria applied by the Cooperative for settlement taxes that affect its activity, with the objective to determine liabilities or contingencies related with tax entity activity. In the Tax Audit were used techniques oriented to proactive critical evaluation within qualitative and quantitative methods, as detailed in an inductive and deductive scheme for abstracting main ideas investigated in the surveys those were generated under a descriptive analysis of the methods used which ones produced research topic, therefore, the need is determined for a tax audit in the Savings and Credit Cooperative Sumak Kawsay. It is important to understand the project in a clear reference for corporate principles transparency where a check of legal documents was displayed against tax procedures Cooperative Savings and Credit Sumak Kawsay systematic and factual. Way, in which one we discover some procedures to verify reported values ones the entity to seek improvements about themselves and maintaining a fiscal management consistent with principles, laws and regulations within the financial institution.